SRR loaded half-mode substrate integrated waveguide monopole slot antenna for multiband applications - V Ramakrishna, T; T P Madhav, B; Venkateswara Rao, M; Babu Rao, A; Sunaina, A; Avinash, A; Shivani, B (International Journal of Engineering and Technology, 2017)
In this article A two layered printed microstrip line monopole slot antenna is proposed for multiband applications. The proposed antenna comprises of size 47*40*1mm with a modified half mode substrate integrated waveguide (M-HMSIW). By changing the slot width at the bottom ground the multiband characteristics has been obtained. A split ring resonator is placed on beside the patch to enhance the characteristics such as gain and bandwidth of the antenna. The proposed antenna works in the region of LTE band (2.1GHz) and WLAN (5.7GHz) and it also holds some applications at x-band applications. The simulated return loss and varied parametric vswr of the proposed antenna has been analyzed using ANSYS EM tool. The simulated results state a peak gain of 22dB and average gain of 5.7 dB. The result of the proposed antenna states that it is the best suitable for various multiband applications